The dynamics of English in Namibia perspectives on an emerging variety - Schröder, Anne (Varieties of English around the world. General series ;, 2021)
"The English language as spoken in Namibia has virtually been overlooked in most textbooks, handbooks, and surveys of varieties of English around the world, or else has only been mentioned in passing. However, this variety of English has recently attracted the attention of several researchers and the present volume brings together most scholars actively involved in the research on English in Namibia from various linguistic fields to present their current research. It covers a wide range of linguistic issues, such as empirical analyses on various levels of linguistic description and use, as well as the application of diverse methodologies, from questionnaire surveys, sociolinguistic interviews and focus group discussions, to corpus linguistics, linguistic landscaping, and digital ethnography. Hence, this book represents the first comprehensive collection of articles and in-depth discussions of this new emerging variety, which contribute to putting this variety on the map of World Englishes but also to advancing general debates in the World Englishes paradigm"--